Old city e Sim city. I simulacri della non-città - Duque, Félix (B@belonline, 2024)
After the ontotheology in which the Modern Age takes shape and culminates, and after its secularization in the mercantilist and trinitarian ontology of Modernity (the Father, who is the Master, the Son, who is the delegate of the enterprise, and the Spirit-Capital), an ontotechnology emerges radiantly, in which the materials of the earth and the humans that inhabit it are technologically transfigured (et Mater Tellus Verbum facta est). The resulting Non-City: Mépolis, supposes the realization of Telépolis, the city at a distance; and it unfolds virtually in Old City, Bit City and Sim City. It is in the latter, in the Simulacrum-City, that the mythical geography of the animatronic Paradise is triumphantly manifested.